MODEL SCAFFOLDING PEMBELAJARAN MENULIS DENGAN PENDEKATAN PROSES BAGI ANAK TUNARUNGU - Yuliyati Endang Purbaningrum Endang Purbaningrum (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The aim for this researach is (1) to describe the needs analysis and challenges and (2) to produce the scaffolding draft model in learning writing using process ap-proach combined with the reflective maternal method (MMR). This research develop-ment applies R2D2 model which emphasizes users’ need based on the context (teacher-student with difable)  and developed collaboratively. Based on the needs analysis in the field in the first year, scaffolding draft model was produced using approach elaborated with the reflective maternal method (MMR).